Sistem Backwash Pada Filtrasi Sistem Pengolahan Air Minum Menggunakan Motor Listrik Pompa Sentrifugal di Perusahaan Umum Daerah Air Minum Tirta Madani Kota Serang - Shafa Yuniar Yasmin; Endi Permata (Pusat Riset dan Inovasi Nasional, 2023)
The need for water consumption is currently very high, almost all human activities require water, therefore the process and production of water is very important to maintain health, the electric motor is the main driving tool needed in the process of cleaning water, therefore the motor is able to move the machine to clean the place water filter or water filter at the Tirta Madani Regional Drinking Water Company in Serang City to maintain water quality. The method used is qualitative by using observation techniques, interviews and literature studies. The filter backwash system is one of the ways to care and maintain the quality of drinking water. Backwashing requires an electric motor, a centrifugal pump and an air blower as its propulsion device.